Penerapan Arsitektur Hijau pada Bangunan Politeknik Teknologi Kimia Industri Medan - Sagala, Peranita; Butar-butar, Theresia (Universitas Medan Area, 2025)
Green architecture, also known as sustainable architecture, is a concept in architecture that has characteristics and focuses on environmentally friendly architecture. The important points of green architecture include minimising the consumption of natural resources, energy efficiency, wise and sustainable use of water, and non-polluting and recyclable materials. In educational buildings, the concept of green architecture is very important to use, not only to reduce emissions and global warming, but also because green architecture significantly influences the performance or comfort of people inside when learning. The purpose of this study is to understand how the concept of green architecture is applied in the buildings of the Polytechnic of Chemical Industry Technology (PTKI) campus in Medan. This study employs a qualitative descriptive method, which involves describing or explaining existing conditions in the field through analysis and extensive discussion to identify results and conclusions. The application of green architecture in buildings is assessed using the Green Building Council Indonesia (GBCI) green architecture indicators. The findings of this study indicate that the PTKI campus meets three main GBCI green architecture indicators: appropriate land use, material sources and cycles, and air quality and comfort.